2020
DOI: 10.1101/2020.08.17.254557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Temperature on the Development of Circadian Rhythms in Honey Bee Workers

Abstract: Circadian rhythms in honey bees are involved in various processes that impact colony survival. For example, young nurses take care of the brood constantly throughout the day and lack circadian rhythms, while foragers use the circadian clock to remember and predict food availability in subsequent days. Previous studies suggested that development of circadian rhythms both in the field and the laboratory began around 7-9 days of age. However, not much is understood about the postembryonic development of circadian… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Although the exact reason is unclear as to why no significant changes in τ and τCV were induced by optic nerve severance at 25°C, it is possible that this particular temperature allows the clock to produce a stable τ, even in the absence of neural information from the compound eye. The crickets were maintained at this temperature throughout their lives and thus could have developed clock characteristics that are suited to this particular temperature, similar to what was found with honey bees (Giannoni-Guzmán et al, 2020). This possibility should be tested by rearing crickets at different temperatures.…”
Section: Role Of the Compound Eye In Locomotor Rhythm Regulationmentioning
confidence: 89%
“…Although the exact reason is unclear as to why no significant changes in τ and τCV were induced by optic nerve severance at 25°C, it is possible that this particular temperature allows the clock to produce a stable τ, even in the absence of neural information from the compound eye. The crickets were maintained at this temperature throughout their lives and thus could have developed clock characteristics that are suited to this particular temperature, similar to what was found with honey bees (Giannoni-Guzmán et al, 2020). This possibility should be tested by rearing crickets at different temperatures.…”
Section: Role Of the Compound Eye In Locomotor Rhythm Regulationmentioning
confidence: 89%
“…Past studies, such as those of Bloch et al (2001) and Moore et al (1998), revealed that the rhythmicity of honey bees changed with age. Additionally, Giannoni-Guzman et al (2020) showed that foragers in the wild display discrete categories that suggest temporal shift work. An earlier study from Giannoni-Guzman and colleagues (2014) compared the endogenous period of three different variants of honey bees ( Apis mellifera carnica , Apis mellifera caucasica and Apis mellifera gAHB ) as well as similarly sized insects from different orders and families.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it makes us consider that the level of sociality in different organisms may play a role in their daily activity patterns. An important emerging feature is that in social insects, be it groups of individuals as defined by their age and job (Moore et al 1998, Bloch et al 2001), or individuals in the same age and task group (Giannoni-Guzman et al 2014, 2020), exhibit differences in their circadian rhythms with functional significance for their sociality. We hypothesize that with increasing levels of social organization, as can be measured in size of the social group, greater levels of individual variation in circadian rhythms will be observed.…”
Section: Introductionmentioning
confidence: 99%